Outcome of Pancreatic Head Coring in as Key Surgical Treatment in Head Dominant Chronic Pancreatitis in Tertiary Referral Centers of Bangladesh - Rabbi, Hashim; Rashid, Md Mamunur; Ahmed, AHM Tanvir; Raihan, HM Sabbir; Nayeem, Sarder Rizwan; Ali, Mohammad; Hakim, HA Nazmul; Chowdhury, Ajmal Quader; Sarder, Mahmud Mohammad (BIRDEM Medical Journal, 2018)
Background: Pancreatic head coring procedure, an organ preserving surgery in which diseased head of pancreas is cored with drainage of main pancreatic duct by lateral pancreatico-jejunostomy. Chronic pancreatitis is a persistently occurring inflammatory disease that causes pancreatic duct stones or calcification, stricture, dilatation of pancreatic duct and irreversible morphological changes resulting intractable pain and losses of exocrine and endocrine function. Appropriate management protocol recognizing underlying pathology, can prevent complications and improves the quality of life. Apart from ductal decompression, in Frey’s’ procedure resection of the “pacemaker of pain” (Head of the pancreas) gives excellent outcome. Methods: In this prospective observational study, we have intended to further validate the Frey’s procedure an effective surgical method in head dominant severe chronic pancreatitis. The study was carried out on 106 Bangladeshi patients who underwent Frey’s Procedure with Lateral Pancreaticojejunostomy from January 2000 to December 2017. Result: The study revealed 51 patients (48.11%) were in 3rd decade of life with 45 male and 61 female. We found 77 patients presented with diabetes mellitus, mostly on insulin. Steatorrhoea was noted in 39 patients and Malnutrition in 79 patients. Visual Analog Scale (VAS) was used for scoring pain. Postoperative morbidity was noted in 29 patients 27.35 % cases, but there was no anastomotic leakage or mortality in the immediate postoperative period in our series. Conclusion: Quality of life has always been the most important decisive factor for patients with severe chronic Pancreatitis. Pain is the predominant clinical feature and very difficult to control. Correction of diabetes and malnutrition are major challenges too. This study revealed, Frey’s procedure with adequate ductal clearance with wide pancreato-jejunal anastomosis in head dominant severe chronic pancreatitis is key to better pain control, improves quality of life and prevents recurrence. Birdem Med J 2018; 8(2): 151-158